The Effectiveness of the Discovery Learning Model Assited by Augmented Reality Media on the Results of Learning Sciense in Recognizing Human Respiratory Organs in Fifth Grade : Efektivitas Model Discovery Learning Berbantukan Media Augmented Reality Terhadap hasil IPAS Mengenal Organ Pernapasan Manusia kelas V - C. Dwi Adi Krisna; Anang Hadi Cahyono; Kadarisman (Prodi Pendidikan Guru Sekolah Dasar, 2025)
This study was conducted due to the low scores in IPAS (Integrated Science) on human respiratory organs in 5th grade, which was attributed to the teacher's reliance on lectures alone and infrequent use of learning media. The aim of this study was to investigate the effectiveness of the Discovery Learning model assisted by Augmented Reality media on IPAS learning outcomes for 5th-grade students learning about human respiratory organs. This study employed a quantitative approach with a quasi-experimental design, specifically a non-equivalent group design. The sample consisted of 18 students in the control group and 22 students in the experimental group. Data collection methods included pretest-posttest, pre-observation, and documentation. The results showed a significant difference in posttest scores between the control and experimental groups, with the control group scoring 61.1 and the experimental group scoring 79.0. The study found a significant effect size of 0.000, indicating that the use of the Discovery Learning model assisted by Augmented Reality media had a significant impact on IPAS learning outcomes. With a significance value of 0.000 < 0.05, the alternative hypothesis (Ha) was accepted, and the null hypothesis (Ho) was rejected. Therefore, there is effectiveness in using the Discovery Learning model assisted by Augmented Reality media on IPAS learning outcomes for 5th-grade students learning about human respiratory organs.